COVID-19: lessons and experiences from South Africa's first surge. Issue 2 (24th February 2021) - Moonasar, Devanand; Pillay, Anban; Leonard, Elizabeth; Naidoo, Raveen; Mngemane, Shadrack; Ramkrishna, Wayne; Jamaloodien, Khadija; Lebese, Lebogang; Chetty, Kamy; Bamford, Lesley; Tanna, Gaurang; Ntuli, Nhlanhla; et al.
Abstract : On 5 March 2020, South Africa recorded its first case of imported COVID-19. Since then, cases in South Africa have increased exponentially with significant community transmission. A multisectoral approach to containing and mitigating the spread of SARS-CoV-2 was instituted, led by the South African National Department of Health. A National COVID-19 Command Council was established to take government-wide decisions. An adapted World Health Organiszion (WHO) COVID-19 strategy for containing and mitigating the spread of the virus was implemented by the National Department of Health. The strategy included the creation of national and provincial incident management teams (IMTs), which comprised of a variety of work streams, namely, governance and leadership; medical supplies; port and environmental health; epidemiology and response; facility readiness and case management; emergency medical services; information systems; risk communication and community engagement; occupational health and safety and human resources. The following were the most salient lessons learnt between March and September 2020: strengthened command and control were achieved through both centralised and decentralised IMTs; swift evidenced-based decision-making from the highest political levels for instituting lockdowns to buy time to prepare the health system; the stringent lockdown enabled the health sector to increase its healthcare capacity. Despite these successes, the stringent lockdown measures resulted in economic hardship particularly for the most vulnerable sections of the population.